Effects of psychological capital and social support availability on anxiety and depression among Chinese emergency physicians: Testing moderated mediation model - Xu, Haibo; Peng, Lixin; Wang, Zhen; Liu, Xin (Frontiers in Psychology, 2022)
Anxiety often precedes depression, and the pathway from anxiety to depression may be affected by multiple exposures. Our research aims to explore the mediating effect of the social support availability between anxiety and depression and how it is moderated by psychological capital. A cross-sectional study was conducted among Chinese emergency physicians at the top-level general hospitals in eastern China. Data were collected via the questionnaire including anxiety and depression subscales of Symptom Checklist-90, Psychological Capital Questionnaire as well as Social Support Rating Scale. The PROCESS v3.4 macro was employed to assess the mediating role of social support availability and a moderating role of psychological capital. A total of 536 valid samples were filtered. Anxiety, depression, social support availability and psychological capital were significant correlated. Anxiety predicts depression (β = 0.82, p < 0.001), and the social support availability mediates the relationship between anxiety and depression (indirect effect = 0.013, 95%BootCI [0.005, 0.024]). Psychological capital further plays a moderating role in the relationship between social support availability and depression (β = 0.06, p < 0.01). Specifically, self-efficacy, hope and resiliency moderate the pathway. The mental health of emergency physicians should be concerned, especially those who have worked up to 10 years. In order to decrease anxiety and depression, Social support availability and psychological capital (specifically, self-efficacy, hope and resiliency) should be increased as the interventions for emergency physicians.